Enhancement of Flood Hazard Assessment through Parameters Modification: A Case Study of the Sikambing Watershed - Fachri, Fiqih Jul; Harlan, Dhemi; Nugroho, Joko; Chaidar, Ana N.; Kasim, Muh. Reysha S. (Journal of Civil Engineering, 2025)
This study focuses on enhancing the flood hazard assessment parameters in Indonesia, particularly within the framework established by the National Disaster Management Agency (NDMA) of the Republic of Indonesia. Given the multifaceted nature of flood hazards, influenced by factors such as land cover change, climate change, and the failure of flood control structures, it is essential to adopt a more comprehensive approach to flood hazard assessment. The research was conducted in the Sikambing Watershed in Medan City, North Sumatra Province, an area that has experienced 12 significant flood events affecting over 13,000 individuals between 2020 and 2024. To improve the flood hazard assessment, this study employs a quantitative method where hydrological and hydraulic analyses serve as the empirical foundation, and flood hazard mapping is carried out by modifying existing parameters to incorporate flood depth (d), flow depth and velocity (dv), and flood duration (T). Additionally, a comparison is made with the flood hazard map based on NDMA parameters to analyze the changes in hazard classification. The resulting flood hazard map indicates a total inundated area of 227.65 hectares; however, the use of different parameters results in significant changes in the proportions of each hazard class. While the low classification dominates both maps, there is an increase in the inundated area classified as medium, covering 17.43 hectares, compared to only 3.25 hectares for the medium hazard classification in the NDMA-based flood hazard map. These results demonstrate that parameter modification provides a more comprehensive picture of flood hazard assessment. This research is expected to contribute to disaster mitigation planning, evacuation strategies and the development of more effective flood control infrastructure.